PROPROTOTYPE DESIGN OF WATER LEVEL CONTROL SYSTEM BASED ON PID CONTROLLER IN PLTMH - Budiastra, Nyoman; Pemayun, A.A Maharta (Journal of Electrical, Electronics and Informatics; Vol 4 No 2 (2020): JEEI (August 2020), 2020)
Abstract— One of the development of technological innovations in the field of control systems in all aspects of life is needed to maintain the stability of the work of a system, PID control to maintain the speed of water flow in the supply pipe in order to maintain the rotating speed of turbines Micro Hydro Power Plants (PLTMH) is very necessary because to maintain the generator rotational speed remains stable. To maintain the stability of the water flow, a sluice gate is needed to regulate the flow of water that comes out of the reservoir to the stockpile, the sluice is called a valve that can be controlled with a microcontroller that will open and close in accordance with the data value of the Water Flow Sensor attached to the pipe. Simulation of Water Flow Sensor with PID control is used to simulate the MHP system with PID control by comparing the output if the PID value is changed.